The Effects of Psychological Contract Breach on Job Satisfaction Among University Employees in Pakistan: Moderating Role of Perceived Organisational Support - Rana Humayyun, Ihsan; Norizan Jaafar, Jaafar; Kartinah, Ayupp; Osman, Bilyaminu (Human Resource Management Academic Research Society (www.hrmars.com), 2020)
This paper investigated the relationship between psychological contract breach (PCB) and job satisfaction (JS) having perceived organisational support (POS) as a moderator. This study employed social exchange theory and organisational support theory to examine PCB, JS and POS relationship. Date collection was made with the help of a self-administered questionnaire from five public sector universities across Pakistan. A sample of 1230 was used for this research study. About 739 valid respondents participated in this research. Structural equation modelling and IBM AMOS was used to carry out analysis. Results showed that PCB led to job dissatisfaction; however, POS did not moderate this relationship. Limitation of this research was its being cross-sectional. A longitudinal study is proposed. Researchers, practitioners are urged to understand PCB, JS and POS relationship in order to have a good employee-employer relationship much needed for the high performance work systems (HPWS)